FOLFIRI plus BEvacizumab or aFLIbercept after FOLFOX‐bevacizumab failure for COlorectal cancer (BEFLICO): An AGEO multicenter study. Issue 11 (14th July 2022) - Torregrosa, Cécile; Pernot, Simon; Vaflard, Pauline; Perret, Audrey; Tournigand, Christophe; Randrian, Violaine; Doat, Solene; Neuzillet, Cindy; Moulin, Valérie; Stouvenot, Morgane; Roth, Gael; Darbas, Tiffany; et al.
Abstract: After failure of first line FOLFOX‐bevacizumab for metastatic colorectal cancer (mCRC), adding either bevacizumab or aflibercept to second‐line FOLFIRI increases survival compared to FOLFIRI alone. In this French retrospective multicentre cohort, we included patients with a mCRC treated with either FOLFIRI‐aflibercept or FOLFIRI‐bevacizumab. The primary endpoint was overall survival (OS), and secondary endpoints were progression‐free survival (PFS), disease control rate (DCR: CR + PR + SD) and safety. We included 681 patients from 36 centers, 326 and 355 in the aflibercept and bevacizumab groups, respectively. Median age was 64.2 years and 45.2% of patients were men. Most patients had RAS ‐mutated tumors (80.8%) and synchronous metastases (85.7%). After a median follow up of 31.2 months, median OS was 13.0 months (95% CI: 11.3‐14.7) and 10.4 months (95% CI: 8.8‐11.4) in the bevacizumab and aflibercept groups, respectively ( P < .0001). Median PFS was 6.0 months (95% CI: 5.4‐6.5) and 5.1 months (95% CI: 4.3‐5.6) ( P < .0001). After adjustment on age, PS, PFS of first line, primary tumor resection, metastasis location and RAS/BRAF status, bevacizumab was still associated with better OS (HR: 0.71, 95% CI: 0.59‐0.86, P = .0003). FOLFIRI‐bevacizumab combination was associated with longer OS and PFS, and a better tolerability, as compared to FOLFIRI‐aflibercept after progression on FOLFOX‐bevacizumab. Abstract : What's new? Second‐line treatment with chemotherapy plus an antiangiogenic agent such as bevacizumab or aflibercept is associated with improved survival among patients with metastatic colorectal cancer (mCRC) who failed first‐line therapy. Here, the efficacy of FOLFIRI plus bevacizumab or aflibercept was investigated in a retrospective, real‐world study in French mCRC patients. Compared to patients who received FOLFIRI plus aflibercept, those who received FOLFIRI plus bevacizumab had significantly improved overall and progression‐free survivals. FOLFIRI plus bevacizumab was also associated with superior tolerability. The findings warrant further investigation to determine whether FOLFIRI plus bevacizumab should be the second‐line therapy of choice for mCRC.